Effects of albumin and weight-standardized hand grip strength on survival for cancer patients with frailty - Xiao-Man Xiong; Chu-Ying Zhang; Hong-Xia Xu; Ge-Ge Zhang; Saba Fida; Jiu-Wei Cui; Wei Li; Min Weng; Kun-Hua Wang; Fu-Xiang Zhou; Jun-Qiang Chen; Xiang-Hua Wu; et al. (Journal of Nutritional Oncology)
Objective:. While albumin and the weight-standardized hand grip strength (HGS/W) serve as valuable prognostic indicators for cancer patients, their correlation with the prognosis in frail cancer patients remains inadequately explored. This study aimed to investigate the prognostic importance of the albumin level and HGS/W in cancer patients with frailty and to further investigate their combined prognostic value. Moreover, this comprehensive evaluation aimed to facilitate timely intervention and treatment for frail patients. Methods:. The research enrolled 5,794 cancer patients identified with frailty from a multicenter research database. The diagnosis of frailty was based on the FRAIL scale. An Albumin-HGS/W score was constructed by combining the albumin and HGS/W values. Cox proportional hazard regression was utilized to examine the association between the albumin level and HGS/W and patient outcomes. Results:. Among these patients, 2,543 were females and 3,251 were males, with a median age of 60.0 years. Optimal stratification based on patient survival revealed the ideal threshold for HGS/W to be 0.48 for males and 0.39 for females, and for albumin to be 38 for both sexes. The fully adjusted model revealed that higher Albumin-HGS/W scores were correlated with a poorer patient prognosis. Notably, an Albumin-HGS/W score of 2 was associated with a higher risk of mortality compared with a score of 0 in the total population (HR: 1.813, 95% CI: 1.580-2.080, P<0.001). Conclusions:. Low albumin or HGS/W values are associated with low survival in cancer patients with frailty. Elevated Albumin-HGS/W scores were linked to decreased survival rates in cancer patients with frailty.